RESYNCHRONIZING THERAPY LONG-TERM RESULTS IN INFANCY TREATED FOR SECONDARY (ARRHYTHMOGENIC) DILATION CARDIOMYOPATHY AFTER SURGICAL INTERVENTION - M. L. Kandinsky; G. A. Efimochkin; O. V. Klycheva; O. V. Kokhtacheva; M. V. Latkin; M. V. Boriskov (Инновационная медицина Кубани)
Secondary dilation (arrhythmogenic) cardiomyopathy in children after artificial pacemaker implantation occurs rather rare. Criteria for implantation are typical: expressed disorders of systemic ventricle function (lowering EF < 35% in dynamics) and prolongation of QRS interval more 120 ms. Heart transplantation is the only alternative. We present 2 cases with successful application of cardioresynchronizer for critical lowering EF at a time of AP implantation. We consider this method will assist in overcoming critical decompensated heart insufficiency and it is a good alternative to the only reliable approach in these children-heart transplantation. The age of patients is not a constraint factor.